Formulation of Lahuna Leave (Eupatorium odoratum) and Sirih Leave Extract (Piper betle L.) as Antiseptic Liquid Soap - Jumrah, Elfira; Abubakar, Andi Nur Fitriani; Agustina, Ayu Safitri; Karneng, Syahdam; Gusti, Herdie Idriawien (Indonesian Journal of Chemical Research, 2023)
Infectious diseases caused by microorganisms are the main cause of high morbidity and mortality in the world. One of the plants that have the potential as an antiseptic is a lahuna leaf. Lahuna leaves contain active antibacterial compounds and the addition of betel leaf to the liquid soap formulations can strengthen the activity of the antiseptic produced. The purpose of this research is to test the effectiveness of liquid soap formulations of lahuna leaves and betel leaves as an antiseptic. The methods used include phytochemical screening, physical observation of liquid soap formulations, and antibacterial activity tests using agar diffusion methods. The results of the phytochemical analysis showed that lahuna leaves contain flavonoids, tannins, terpenoids, and alkaloids, while betel leaves contain flavonoids, saponins, tannins, terpenoids, and alkaloids. The liquid soap formulation of lahuna leaves and betel leaves has a clear yellow color, distinctive aroma, liquid form, rough taste, and lots of foam and has very strong inhibition against Staphylococcus aureus which is characterized by clear zones formed for each formulation I (22.4 mm), formulation II (21.8 mm) and formulation III (20.1 mm). These results indicate the potential of liquid soap formulations of lahuna leaves and betel leaves as antiseptic soap.